An Analysis of Critical Thinking skills in General Education Course - Pislae-ngam, Kattakamon (Advances in Social Sciences Research Journal, 2018)
Critical thinking is an important skill that students need to be developed along with learning. The purpose of this research was to analysis of critical thinking skills in General Education course. The samples consisted of 132 students were selected by the cluster sampling technique. who studied in undergraduate students registered in General Education course first semester academic year 2017. The instruments used in the research were questionnaire. The findings of the study indicated that the overall critical thinking skills of students in General Education course are in the fair degree with average scores ranging from 16-20 for 38.63%. There are 9.09-22.72% students who required to make improvements in their critical thinking skill. The results from the study of each elements revealed that the students in General Education course are able to make the highest scores 21.97% and  lowest scores 3.79 in awareness of uncertainties based on logic.  in identifying the unmentioned statements and assumptions. Thus, the results can be developed and inserted in the teaching and learning in the next course.